Radical Innocence : A Critical Study of the Hollywood Ten - Dick, Bernard F. (Book collections on Project MUSE., 1989)
On October 30, 1947, the House Committee on Un-American Activities concluded the first round of hearings on the allege Communist infiltration of the motion picture industry. Hollywood was ordered to ""clean its own house, "" and ten witnesses who had refused to answer questions about their membership in the Screen Writers Guild and the Communist party eventually received contempt citations. By 1950 the Hollywood Ten, as they quickly became known, were serving prison sentences ranging from six months to a year. Since that time the group, which included writers, directors, and a producer, have be